STRATEGI PENGUSAHA RUMAH BATIK DEWI BUSANA DALAM MEMAJUKAN USAHANYA DI KECAMATAN LUNANG KABUPATEN PESISIR SELATAN - Handayani, Afrila; Sarbaitinil, Sarbaitinil; Elfemi, Nilda (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
Changes and developments caused by foreign cultures turned out to have an impact on people's mindsets, one of which was to entrepreneurs of batik craftsmen. This impact changed the ways and strategies in managing their batik business, both in terms of production, distribution and marketing. The purpose of this study was to describe the strategy of the Dewi fashion batik house entrepreneur in advancing her business in the Lunang District, Pesisir Selatan Regency. The theory used in this study is the theory of economic action proposed by Max Weber. The research was conducted in Lunang District, Pesisir Selatan Regency,. This study uses qualitative research methods with descriptive research type. The withdrawal of informants was carried out by purposive sampling technique. The data collection method in this study began with observation, in-depth interviews, and document studies. Data analysis was carried out in several stages, namely, data collection, data reduction, data presentation and drawing conclusions. The results showed that there were several strategies of entrepreneurs in developing the Dewi Busana batik house, Lunang District, Pesisir Selatan Regency. Among them are by increasing human resources, and doing marketing of production through social media, and fashion show events. In addition, in developing batik houses, there are also several obstacles, such as the difficulty of meeting consumer needs in large production and the difficulty of obtaining raw materials.